PATH-65. MOLECULAR SIGNATURE OF FAT1 RELATED MOLECULES IN GLIOMAS IN THE CONTEXT OF THE WHO 2016 CLASSIFICATION - Chosdol, Kunzang (Neuro Oncol, 2019)
Glioblastoma (GBM, WHO grade-IV) being the most malignant and aggressive form of glioma remains a major clinical challenge, with an overall 5-year survival rate of only 9.8%. Till recently, glioma diagnosis and grading were solely dependent on the phenotypic and histological features. However, with the advancement in the understanding of the molecular biology of glioma several molecules have been identified. The importance of these molecular/genotypic features of the tumor became evident by the inclusion of these molecular features by World Health Organization (WHO) in 2016 in glioma sub-grouping. Our lab is focused on studying the role of FAT1 gene (human ortholog of Drosophila tumor suppressor gene, fat) in glioma biology and aggressiveness. We observed FAT1 gene to have an oncogenic role in glioma where it has been found to upregulate migration/invasion, inflammatory microenvironment of the tumors, HIF1α expression/activity in the tumor-cells under severe hypoxia and in regulating EMT/stemness properties of GBM-cells under hypoxia. Here, we have characterized the molecular relationship between FAT1 related molecules and known- molecular markers of glioma with the hope of identifying glioma subgroup with a molecular signature of clinical significance by (i) analyzing the expression correlation of FAT1 and FAT1 regulated pro-inflammatroy molecules like COX2, IL1b and IL6 with the known- molecular markers of glioma like p53, IDH1, MGMT, EGFR, TERT in low-grade (grade-II) and high-grade (grade-III/IV) gliomas (n=50) by real-time PCR, sequencing, immunohistochemistry and in-silico analysis of TCGA-GBM-data (ii) Analyzed the regulatory role of FAT1 on the above known markers by siRNA mediated knockdown of FAT1 in in-vitro cell-culture system and (iii) further analyzed the identified molecular signature for their correlation with the patients prognosis/survival in the follow up patients. We observed a novel molecular signature with significant correlation with patients’ clinical outcome. Therapeutic targetting of FAT1 may benefit patients with high FAT1 expressing tumors.